Understanding on toughening mechanism of bioinspired bulk metallic glassy composites by thermal spray additive manufacturing. (1st March 2020) - Zhang, Cheng; Wang, Wei; Xing, Wei; Liu, Lin
Abstract: Toughening mechanism of bioinspired bulk metallic glassy composites (BMGCs) reinforced with various volume fractions of ductile stainless-steel (SS) phase fabricated via newly developed thermal spray additive manufacturing was investigated. Microstructure characterizations and nanoindentation suggested a strong interface-bonding along with nanoscale compositional gradient formed between the metallic glass and SS phases. Finite element modelling and theoretical analysis revealed that the increase in toughness arose from the nacre-like soft/hard phase configuration, which exhibits the effective stress-shielding effect against crack propagation, thus mitigating stress concentration and blocking crack propagation. Graphic abstract: Image, graphical abstract